Lifelong learning targets of education 2030 agenda and policy-implementation modalities in Nigeria (2018)
Education 2030 Agenda, popularly tagged the "Incheon Declaration ", is the new vision of education agreed upon by over I, 600 participants from 160 countries at World Education Forum held in Republic of Korea from 19-22 May, 2015 with the theme “Towards inclusive and equitable quality education and lifelong learning for all". This paper critically examined the lifelong learning opportunities for all targets of the Agenda and discussed policy directions and implementation modalities for achieving the cardinal focus areas of the targets. The paper began with the examination of the components of access, equity and inclusion, quality and learning outcomes, and lifelong learning for all opportunities. It also examined the lifelong learning opportunities targets of the Agenda and identified the pillars upon which the targets are anchored. The recommendations on policy direction and implementation modalities for each of the pillars were suggested. The paper was concluded with the submission that adult education, adult learning and training opportunities, literacy, education for sustainable development, global citizenship education framework must be given utmost priority in order to achieve the targets of the lifelong learning opportunities for all in Nigeria